Stress wave propagation test and numerical modelling of an underground complex - Resende, R. (2014)
Ground vibration is the most important environmental effect of blasting, and tools for its understanding and control are a prime necessity for the excavation of tunnels and caverns in hard ground. This paper contributes to an improved understanding of the way waves travel in the ground, particularly when there are excavations in the path of propagation, while also enhancing existing numerical models to better simulate that behaviour and thus provide better means to address underground vibration impacts. To this purpose, twenty low intensity blast between neighbour tunnels of an underground complex were performed, followed by a numerical study of the test. The test and simulation showed that, contrary to what is implied in semi-empirical attenuation laws, factors like the propagation path or local amplification can be more important than instant explosive weight and distance to blast.